Mechanism of Abnormal Coagulation Induced by Tigecycline in Cancer Patients - Sun, Li-Hua; Bai, Kun-Hao; Wu, Guo-Yan; Tian, Xiao-Peng; Zou, Zhi-Qing; Wang, Da-Wei; Dai, Yu-Jun; Chen, Si-Liang (Frontiers in Pharmacology, 2022)
Tigecycline is a broad-spectrum antibiotic via intravenous administration and also effective in hospitalized patients with methicillin-resistant staphylococcus aureus. However, emerging evidence from Phase 3 and 4 clinical trials, tigecycline is associated with increased all-cause mortality versus the comparator group, especially in tumor patients. The reason for the excess death of tigecycline in those trials is not yet clear. Due to the interaction between tumor and coagulation dysfunction, we hypothesized that tigecycline-induced coagulopathy may play a key role in tumor patients. In this study, we found that tigecycline usage could cause abnormal coagulation index in tumor patients in our hospital, especially those with hematological malignancies. Patients with tigecycline showed abnormal coagulation parameters, including hypofibrinogenemia, reduction of platelet counts, and prolonged activated prothrombin time (APTT), thrombin time (TT) and D-dimer. Notably, patient's coagulation disfunction could gradually recover after tigecycline discontinuation. From functional studies, we found that tigecycline inhibits platelet adhesion and aggregation. Bulk RNA sequencing results suggested that tigecycline could significantly regulate the expression of genes related to platelet function pathways. In addition, we demonstrated that tigecycline increases the frequency of single nucleotide polymorphisms and the number of alternative splices in CHO cells. Taken together, these data illustrated that the mechanism of tigecycline-induced coagulopathy in tumor patients. Meanwhile, a warning should be given when doctors applied tigecycline to control infections for tumor patients in clinic.